A migratory shark bone. (23rd June 2018) - Mathew, Elizabeth; Myuran, Tharsika; Ching, Hoi-Yi
Abstract : Fish bone ingestion is a common presentation in ENT. If not managed correctly, it can cause serious complications for the patient and dilemmas for the clinician. A 49-year-old Sri Lankan woman presented to the emergency department following shark bone ingestion with a 'pricking' sensation in her throat. After initial investigation, the bone migrated through to the sternocleidomastoid muscle. After surgical removal of the shark bone she went on to develop a large neck collection, which required surgical drainage. The careful attention to the patient's history and use of imaging facilitated treatment in this case of fish bone ingestion and management of the sequelae.